1995
DOI: 10.1259/dmfr.24.4.9161171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of image magnification of digitized bitewing radiographs on approximal caries detection: an in vitro study.

Abstract: Digital image magnification has a significant influence on observer performance in the detection of approximal caries, with an upper limit beyond which diagnostic accuracy may be reduced. Further research is needed to determine limits for various different diagnostic tasks so as to give GDPs guidelines on the appropriate magnifications to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 9 publications
2
15
0
4
Order By: Relevance
“…9 This finding was similar to our results, although another study also determined the upper limit of zoomed digital image to be 12 £ , 13 greater than the results of this study. The comparison between the present study with these papers is limited, however, because they are related to different tasks and the software used for capture and imaging interpretation is also different.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…9 This finding was similar to our results, although another study also determined the upper limit of zoomed digital image to be 12 £ , 13 greater than the results of this study. The comparison between the present study with these papers is limited, however, because they are related to different tasks and the software used for capture and imaging interpretation is also different.…”
Section: Discussionsupporting
confidence: 89%
“…4 -7 The zooming function comes in a software for image magnification or reduction 8 and in some studies has been shown to provide improvement of the diagnosis efficacy of initial caries lesions 9,10 and detection of small endodontic files in relation to the radiographic apex. 11 However, the digital magnification did not affect the detection of root fractures 12 and both Moystad et al 13 and Scaf et al 9 showed the limitation of zoomed digital function for radiographic interpretation of caries lesions.…”
Section: Introductionmentioning
confidence: 95%
“…Besides, the use of magnification on the digital images has not been justified. Previous studies have shown that diagnostic information will often be lost with magnification of digital images [Møystad, 1995]. Magnification may have been employed to avoid introducing a bias between the evaluated imaging modalities, both analog and digital, yet it was not uniform (E2 vs. E6).…”
Section: Discussionmentioning
confidence: 99%
“…By further specifying the technical parameters to be applied for the monitors, variabilities that may arise from the switching of monitors were avoided [Møystad et al, 1994;Versteeg et al, 1997a]. We selected a constant image size based on previous studies, which indicated a significant difference between approximal caries diagnosis obtained from images with different magnification [Møystad et al, 1995;Svanaes et al, 1996]. Further, in the present study we used black image surroundings because we noted a difference in observer…”
Section: Discussionmentioning
confidence: 99%